A diagnosis that is so easy yet missed till 4th decade! - Deepthi Mangesh; R Keshava; Nagaraj Desai (Wolters Kluwer Medknow Publications, 2019)
A case of coarctation is described which was diagnosed in the fourth decade. A simple examination of the lower limb pulses and for radio-femoral delay with due diligence in this hypertensive patient could clinch the clinical diagnosis; yet it was missed in the preceding years. He underwent coarctoplasty with stenting with satisfactory short term result.